Estudo do papel da via da p38/MAPK no crescimento dos gliomas in vitro - Grave, Nathália (2022)
Gliomas constitute a heterogeneous group of central nervous system (CNS) tumors, being the most aggressive and lethal among primary tumors. Glioblastoma multiforme (GBM), the most common subtype in adults, has a poor prognosis due to the tumor's high recurrence rates, as well as its resistance to conventional treatments such as chemotherapy and radiotherapy. Although they are still not fully understood, it is known that mutations in important regulatory networks are related to the appearance of gliomas. One of the most important pathways regulating the genesis and progression of gliomas is the mitogen-activated protein kinases (MAPKs) pathway. Among these, the p38/MAPK pathway is implicated in antagonistic effects such as cell proliferation and survival. In view of these findings, as well as the need to seek new therapeutic targets for gliomas, this study aimed to investigate the role of the p38/MAPK pathway inhibition in the growth of gliomas in vitro. For this, glioma cell lines and primary cultures of human glioma were used. These were treated with the selectives inhibitors of the pathway, skepinone-L and ML3403, and/or the alkylating agent temozolamide (TMZ) (100 μM) and subsequently irradiated (2 Gy). The effects on cell viability and proliferation, colony formation and cell cycle and death at different times (24 and 48 h) were evaluated. The results showed that the skepinone-L inhibitor at different concentrations, in single or combined treatment, decreased cell viability and proliferation, and reduced the potential for colony formation in the studied glioma cells. This effect, however, was not able to sensitize the cells when treated in association with TMZ. There were also alterations in the cell cycle, with a delay in the S and G2 phases, and an increase in the percentage of cells in late apoptosis/necrosis compared to the treatments used. Results with the p38 inhibitor ML3403 showed a reduction in cell proliferation, it sensitized radioresistant cells when treated in combination with irradiation, altered cell cycle progression, and increased apoptosis in glioma cell lines. Thus, in view of the results obtained regarding the reduction in the growth of the studied cells, the inhibition of the p38/MAPK pathway appears as a potential target for the treatment of gliomas. Further studies are needed to better understand its role in the glioblastoma tumor microenvironment.